Identification of Plasma Protein Biomarkers of Acute Renal Allograft Rejection. (July 2018) - Rossetti, Maura; Fitzpatrick, Connor; Harre, Nicholas; Zheng, Ying; Mercer, Neil; Sunga, Gemalene; Gjertson, David; Reed, Elaine
Abstract : N/A: Upon presentation of clinical symptoms, renal transplant recipients routinely undergo needle core biopsy to diagnose acute graft rejection. This procedure is invasive and associated with patient morbidity. We aimed at validating a panel of plasma proteins as a minimally invasive and cost-effective set of biomarkers to rule out renal allograft rejection. Based on a mass-spectrometry-based pilot study, 8 proteins were selected to be tested by ELISA in 164 adult renal transplant recipients, including 91 non-rejectors and 73 rejectors. The rejectors were sampled at the time of rejection (−7/+3 days of a positive biopsy) or after the event (>30 days after the positive biopsy). The non-rejectors were sampled +/− 30 days from the negative biopsy. We were able to confirm statistically significant differences both cross-sectionally and longitudinally in Apolipoprotein A1 (ApoA1), as we previously published. In addition, we found statistically significant differences in alpha-2-Macroglobulin (A2M), C1-inhibitor and ITIH4 cross-sectionally, and in Alpha-1-Antichymotrypsin and ApoA1 longitudinally. Next, we sought to determine whether combinations of these markers could be used to classify patients as rejecting or non-rejecting. Multivariate logistic regression and CART analyses demonstrated that a panel including ApoA1, A2M and C4 had the best classification performance (AUC = 0.785). Similar results were obtained in a cohort of pediatric renal transplant recipients (AUC = 0.787). In conclusion, a combination of plasma proteins could be used to rule out acute renal allograft rejection. Our data warrant further validation of this new method in a larger independent renal transplant cohort, both adult and pediatric.